"Pointing at Shadows": Wallace, Wittgenstein, and the Problem of Putting Pain into Words. Issue 2 (15th March 2023) - Chase, Greg
ABSTRACT: This article demonstrates that the philosophy of Ludwig Wittgenstein exerted an important – and under-recognized – influence on David Foster Wallace's fictive representations of clinical depression. In particular, Wittgenstein's inquiry into the question of how private pain might be publicly communicated informs Wallace's recurrent preoccupation with how the experience of depression might be coherently put into words. After briefly examining Wallace's strategies for representing depression in his early story "Planet Trillaphon as it Stands in Relation to the Bad Thing" (1984) and in Infinite Jest (1996), my discussion turns to "The Depressed Person" (1999), which I read as Wallace's most ambitious effort to find language for the inner experience of clinical depression. My article considers "The Depressed Person" alongside Elizabeth Wurtzel's memoir Prozac Nation (1994), challenging the received view that Wallace's story operates as a straightforward attack on Wurtzel and reading it instead as a kind of tribute.